Interaction of the Antibiotic Rifampicin with Lipid Membranes - Rui M. S. Santos; Jaime Samelo; Alexandre C. Oliveira; Margarida M. Cordeiro; Maria Julia Mora; Gladys E. Granero; Hugo A. L. Filipe; Luís M. S. Loura; Maria João Moreno (Biomolecules)
Rifampicin is a broad-spectrum antibiotic, active against several bacterial infections such as tuberculosis. It is a relatively large and structurally complex molecule, including numerous polar groups. Although violating several of Lipinski’s rules for efficient intestinal absorption, rifampicin shows good oral bioavailability, permeating through cell membranes in the absorption pathway and those of the target organisms. Some hypotheses have been proposed for its efficient membrane permeation, but the details are mostly unknown. In this work, the interaction of rifampicin with POPC lipid bilayers is studied using experimental biophysics methodologies and atomistic molecular dynamics simulations considering the two most prevalent ionic species at physiological pH, the anionic and the zwitterionic forms. The results show that both ionization forms of rifampicin establish favorable interactions with the membrane lipids, in agreement with the relatively high partition coefficient obtained experimentally. The results from MD simulations and isothermal titration calorimetry using different pH buffers show that the piperazine group inserts deeply in the membrane and is accompanied by a stabilization of its neutral form. The bulky nature of rifampicin and its deep insertion in the membrane lead to a strong perturbation in the lipids local order, decreasing the membrane barrier properties as evaluated from the rate of carboxyfluorescein leaching. Altogether, the comparison between the experimental and MD simulations results provides important insight regarding the rifampicin molecular features responsible for its relatively fast membrane permeation. The lipid POPC used in this study was selected as a simple membrane with relevance for different organisms across all kingdoms. Further studies using more complex lipid compositions will provide details on eventual specificities for rifampicin interaction with the membranes of distinct organisms.